#QuédateEnCasa, because it's not just flu: The impact of cognitive authorities' communication on human behaviour during the pandemics - Böhmer, Kristína (Diskuze v psychologii, 2021)
The main objective of this study is to point out the importance of communication by cognitive authorities, in this case of political elites, during the health crisis. Their rhetoric can have an enormous impact on the behaviour of the general population. If these cognitive authorities recommend following the advice of health authorities, people are more likely to follow the advice. This can come out as a crucial factor in preventing the spread of the virus during any epidemics. A virus could be more predictable if human behaviour were predictable as well. Confirming the impact of cognitive authorities on the general public's behaviour during a health crisis might help us understand what needs to be done differently by those political elites if there will be any other health crisis in the future.
Keywords: Evaluation Studies as Topic; Spain; Španělsko; vládní regulace; Government Regulation; lidé; Communicable Disease Control; vůdcovství; zdravotní politika; Social Media; Slovenská republika; Communication; COVID-19; hodnotící studie jako téma; komunikace; Humans; Health Policy; sociální média; Leadership; kontrola infekčních nemocí; Slovakia; Knowledge Management; management znalostí